A Rare Case Presentation of a Perforated Giant Sigmoid Diverticulum - Jennifer C. Kam; Vikram Doraiswamy; Robert S. Spira (Case Reports in Medicine)
Giant sigmoid diverticulum (GSD) is a rare complication of diverticulosis. These lesions arise from herniations of the mucosa through the muscle wall which progressively enlarge with colonic gas to become large air-filled cysts evident on plain X-ray and CT scans. We present a rare case of a 72-year-old female presenting with abdominal distention, abdominal tenderness, and fever who developed a type 1 giant sigmoid diverticulum (pseudodiverticulum) that subsequently formed an intra-abdominal abscess and an accompanying type 2 diverticulum as well. The patient was treated with surgical resection of the diverticulum with a primary anastomosis and abscess drainage. The patient’s postoperative course was uneventful. This case helps to support the need for the consideration of GSD in patients aged 60 and older with a history of diverticulosis and presenting with abdominal discomfort and distension.